(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Body is assembled by Vata Pitta and Kapha Dosha each assigned to do its Kshaya, Poshana and Dharana Karma. Vata dominates both because of its Yogavahi Guna. Pakshaghata is one of the grievous Vata Vyadhi in Ayurveda. Sansarga of other Dosha and Dhatu leads to involvement of Shodhana and Shaman Chikitsa. Snehana therapy, Bahya and Abhyantar are well known for its treatment in Vata Vyadhi. Inclination towards modernization and deviation from basic healthy life make the body vulnerable for disease especially Vata Vyadhi. We know Vata Vyadhi are fulminate in nature but early diagnosis with the help of investigation tools like CT scan, MRI etc; we can prevent from further damage caused by previous pathology. Sansarga of other Dosha and Dhatu leads to involvement of Shodhana and Shaman Chikitsa. In terms of treatment Virechana had been mentioned as Shodhana Chikitsa in our Samhita. Here an attempt was made to apply Virechana treatment with two different Poorva karma and to evaluate the efficacy with an applied aspect. The study had been conducted on 30 patients of Pakshaghata (Hemiplegia) who were divided in two groups and were given below treatments nearly for 1 month. Group A: Virechana followed by Shashtik-Shali Pindasweda. Group B: Virechana followed by Abhyanga. It was observed that both groups are effective in Ruja, Gauravta and Cheshtanivriti in the management of Pakshaghata (Hemiplegia) but Group A is more effective in comparison to Group B.